Shrinkage mechanism of red clay based on changes in the thickness of bound water film - Yabin Zhang; Shuangying Zuo; Daoyong Wu; Guosheng Yang (地质科技通报, 2023)
Objective The content and existence form of bound water have an important influence on the physical and mechanical properties of red clay, and macroscopic shrinkage of red clay leads to microstructure changes of soil particles, pores and bound water, which in turn may cause soil surface cracking, triggering infiltration, destabilization, and other engineering geological problems. Methods Thermogravimetric analysis tests, BET tests, scanning electron microscopy (SEM) and zeta potential tests were conducted to study the variation characteristics of bound water during the shrinkage of undisturbed red clay. The structural model of spherical and lamellar clay particles based on the uniform distribution of bound water film was established, and the formula for the calculation of bound water film thickness was derived. Results The results showed that most of the water in undisturbed red clay exists in the form of bound water and the loss of weakly-bounded water continues throughout the shrinkage process of red clay. During the process, the zeta potential, specific surface area and the thickness of the bound water film decreased continuously. Conclusion The results reveal the intrinsic mechanism of water loss and shrinkage of red clay, which can provide theoretical support for solving environmental engineering geological problems.